(untitled) (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2019)
Teachers of all subjects face one common problem: student engagement. Because students need to be engaged to effectively learn, teachers need to know the best way to engage students in learning. In the English Language Arts classroom, teachers are faced with the problem of engaging students in reading texts that are sometimes not interesting or relevant to their lives. These teachers are tasked with finding ways to make these texts more engaging, or deciding to use more culturally relevant texts. Research has found that culturally relevant texts and teaching methods engage and therefore more effectively teach students. How do teachers make canon texts more culturally relevant to students and how do teachers use culturally relevant texts to teach their students?